Expression Analysis of and Genes in Oral Squamous Cell Carcinoma Patients - Omid Ghasemi; Fatemeh Karami; Iman Salahshourifar; Mohammad Nooridaloii (Journal of Sciences, Islamic Republic of Iran)
Oral squamous cell carcinoma (OSCC) is still one of the leading cancer related death, worldwide. Owing to the critical role of ALDH1 isoforms in pathogenesis of cancers and controversies in previous reports, the present study was conducted to determine the expression of two challenging ALDH1 isoforms in OSCC tissue samples. RNA was isolated from 30 OSCC and normal fresh tissues margins and then was converted to cDNA using Thermo Scientific™ Fermentas cDNA synthesis kit. Reverse Transcription Real time polymerase chain reaction (RT-Real time PCR) was performed on synthesized cDNA using primer pairs specific to ALDH1A1 and ALDH1A3 genes. It was found that the ALDH1A1 mRNA expression was significantly higher in OSCC samples compared to normal margins (P-value= 0.001). ALDH1A1 and ALDH1A3 expression was significantly associated with alcohol drinking (P-value= 0.01) and smoking (P-value=0.008), respectively. There was no correlation among ALDH1A1 and ALDH1A3 expressions and clinicopathological features (p-value>0.05). Confirmation of the over-expression ofALDH1A1 isoformin OSCC samples maybe indicating that it plays critical role in pathogenesis of OSCC. However, owing to the discrepant findings on the association of ALDH1A1 expression with clinicopathological features, further studies are required to identify its role as driver or passenger carcinogenic alteration and its exact association with smoking.